First two species of Austroleptis Hardy (Diptera: Brachycera: Austroleptidae) from Brazil - Fachin, Diego Aguilar; Santos, Charles Morphy D.; Amorim, Dalton De Souza (Zootaxa, 2018)
Two new species of the genus Austroleptis Hardy, so far known only from Australia and Chile, are described from the Brazilian Atlantic Forest—A. longirostris nov. sp. and A. papaveroi nov. sp. The species share clear apomorphic features of the genus, as the subdivision of female tergite 8. Both new species share a distinctive wing pattern, and a flagellomere 1 that is as wide as the more distal flagellomeres, features that clearly differentiate them from the Chilean and Australian species. It is likely that the Brazilian species compose a small clade apart from the Chilean species of the genus. A. longirostris nov. sp. has a particular long proboscis, even for the standards of non-tabanid tabanomorphs, while A. papaveroi nov. sp. has a stump on M3. The scutum coloration also helps to discriminate between both species. This is an additional example of a group in southern Brazil with southern temperate connections, i.e., involving southern Chile and Argentina and either Australia, New Zealand or both. Additional records and illustrations of Austroleptis atriceps Malloch and           A. penai Nagatomi & Nagatomi from Chile are provided.